The Aglipayan Church in Dumangas, Iloilo, 1902-1940 - De La Vega, Eric Dumile
This is a historical-descriptive study of the Aglipayan Church in Dumanagas 1902-1940, focusing on its beginning, growth and decline. The following questions are raised: What conditions/events preceded the founding of the Aglipayan Church in Dumangas? What were the basic differences and similarities between the Catholic and the Aglipayan Church? Lastly, what factors contributed to the growth and decline of said church?, The data gathering techniques used in this study were: formal and informal in-depth interviews with key informants and the use of secondary sources in the absence of primary data. Official documents of the Aglipayan Church primary data. Official documents of the Aglipayan Church were also used as well as observation of the Aglipayan rites and ceremonial practices. Investigations revealed that socio-political, economic and religious conditions earlier paved the way for the establishment and acceptance of the Aglipayan Church in Dumangas. Several factors were identified as contributory to the growth of the Aglipayan Church, namely: a) growth of nationalism as triggered by the illustrados, b) the friendly attitude of the American Colonial Government, c) the conversion of the Catholic friar of Dumangas, Rafael Murillo, OSA, d) support of the local elites to the new church and lastly, e) the close resemblance of the Aglipayan practices to the Catholic faith. (p)The Aglipayan Church is different from the Roman Catholic in that, it is nationalistic in perspective and rationalistic in approach. Its similarities lies in the rituals and ceremonial forms found in the sacraments. It was these external similarities which attracted the Dumangas folk to the new religion. Sadly, however, the phenomenal growth of the Aglipayan Church did not last long. Many external and internal factors contributed to its decline. These were: a) the countermoves of the Catholic Church, b) the failure of the Aglipayan leadership to understand the value of education, c) the failure to develop national programs which brought about a weak central structure, d) the weakening of its inner vitality due to the waning of nationalism and, e) the influx of other religions. Some questions however remains to be asked: Can the Aglipayan Church recover its lost vitality? How and by what means? Whether this questions can be answered or not, there is one we can be sure of. The Aglipayan Church in Dumangas and its sister churches all over the country, were able to carve a niche for themselves in the annals of Philippine history. It is the first and the last and the only nationalistic church in the country.